2019
DOI: 10.1186/s12199-019-0776-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between lifestyle, parental smoke, socioeconomic status, and academic performance in Japanese elementary school children: the Super Diet Education Project

Abstract: Background Health and education are closely linked. However, few studies have explored the correlates of children’s academic performance in Japan. We aimed to investigate comprehensively the associations of low academic performance among school children with lifestyles, parental smoke, and socioeconomic status. Methods In 2016, children aged 6 to 13 years from the Super Diet Education School Project were surveyed using questionnaires. The survey explored the lifestyles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 30 publications
(43 reference statements)
0
31
0
Order By: Relevance
“…These relationships have been identified and supported by the findings of other researchers in a variety of settings. In a recent study conducted in Japan, Yamada and collaborators showed that children s poor lifestyles and low socioeconomic status were significantly associated with low academic performance among Japanese children [19]. In separate studies, also in Japan, Nakahori et al, concluded that a good home environment relates to children s good dietary behaviors, positive lifestyle factors, and good overall health.…”
Section: Discussionmentioning
confidence: 99%
“…These relationships have been identified and supported by the findings of other researchers in a variety of settings. In a recent study conducted in Japan, Yamada and collaborators showed that children s poor lifestyles and low socioeconomic status were significantly associated with low academic performance among Japanese children [19]. In separate studies, also in Japan, Nakahori et al, concluded that a good home environment relates to children s good dietary behaviors, positive lifestyle factors, and good overall health.…”
Section: Discussionmentioning
confidence: 99%
“…January 2016) [10,20] and who belonged to one of five elementary schools in Takaoka City, Japan participated in this study. The Super Shokuiku School Project was designed to investigate food education and was supported by the Japanese Ministry of Education, Culture, Sports, Science and Technology (MEXT).…”
Section: Methodsmentioning
confidence: 99%
“…Social background was assessed based on the following items: Mother's employment status, family structure, perceived family affluence, communication with parents, individual parental internet usage at home h/day (i.e., both the mother and father), and parental health behaviors according to Breslow (1980) (i.e., both the mother and father). The item concerning "mother's employment status" [20,22] included three response categories (i.e., "full-time," "part-time," and "unemployed (housewife)"), while "family structure" [22,23] was categorized as either "three-generation family" or "nuclear family." Further, "socioeconomic status" was determined according to perceived "family affluence" [20,22] (i.e., "affluent," "neither," or "not affluent"), while "communication with parents" [22,24] was categorized as either "often" or "rarely."…”
Section: Social Background and Parental Lifestylesmentioning
confidence: 99%
See 2 more Smart Citations